An Examination of the Status of Organizational Communication Programs in Texas Colleges and Universities - Smith, June Hubbell ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
A study was conducted to determine if the speech communication programs in Texas colleges and universities were providing the skills needed by industry. A survey of current business journals revealed seven skills needed by college graduates seeking employment in business: (1) public speaking skills, (2) knowledge of communication theory and flow of messages through organizations, (3) interviewing skills, (4) small group meeting skills, (5) dyadic communication skills, (6) listening skills, and (7) leadership skills. Forty-one 1982 undergraduate and 16 graduate college catalogs were examined to discover the number and percentages of Texas degree programs offering business communication-related courses and to compare the description of the skills focused upon in the business-related communication courses to the seven skills listed as needed by the journal review. Except for courses in persuasion/sales presentations and small group discussion and for skills in business-related oral reports and group meeting, all results showed that Texas college speech programs were not meeting the stated communication training needs of business and industry. It would appear that these programs need curriculum additions. (JL)
ERIC Note: Paper presented at the Meeting of the Texas Speech Communication Association (Houston, TX, October 7-9, 1982).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Business Communication; Communication Research; Course Content; Curriculum Evaluation; Education Work Relationship; Educational Needs; Higher Education; Job Skills; Speech Communication; Speech Curriculum; Speech Skills; Texas; Reports, Research; Speeches/Meeting Papers